2022
DOI: 10.3390/biomedicines10092155
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of H2S and Recombinant Human Hsp70 on Inflammation Induced by SARS and Other Agents In Vitro and In Vivo

Abstract: The ongoing epidemic caused by SARS-CoV-2 infection led to the search for fundamentally new ways and means to combat inflammation and other pathologies caused by this virus. Using a cellular model of lipopolysaccharide (LPS)-induced sepsis (human promonocytes), we showed that both a hydrogen sulfide donor (sodium thiosulfate, STS) and a recombinant Heat shock protein 70 (rHsp70) effectively block all major inflammatory mediators when administrated before and after LPS challenge. The protective anti-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Interestingly, in our experiments administration of recHsp70 significantly reduced LPS-induced TLR4 expression in human macrophage cells (THP1) [181]. The ability to eliminate damaged proteins and prevent the formation of aggregates of different nature is obviously the most important protective function of Hsp70 described for such diseases as AD, Parkinsonism, ALS, and many others.…”
Section: Molecular Mechanisms Underlying Protective Effects Of Hsp70 ...mentioning
confidence: 52%
See 3 more Smart Citations
“…Interestingly, in our experiments administration of recHsp70 significantly reduced LPS-induced TLR4 expression in human macrophage cells (THP1) [181]. The ability to eliminate damaged proteins and prevent the formation of aggregates of different nature is obviously the most important protective function of Hsp70 described for such diseases as AD, Parkinsonism, ALS, and many others.…”
Section: Molecular Mechanisms Underlying Protective Effects Of Hsp70 ...mentioning
confidence: 52%
“…Along these lines, in our experiments on a small sample of Covid patients [181], we have recently demonstrated that hot helium inhalation inducing Hsp70 followed by inhalation of hydrogen sulfide donor has a pronounced therapeutic effect preventing lung fibrosis in the patients. Moreover, in our in vitro and in vivo experiments we showed that different hydrogen sulfide donors as well as recHsp70 significantly reduced the level of proinflammatory cytokines, ROS, and other consequences of LPS-induced inflammation [181].…”
Section: Molecular Mechanisms Underlying Protective Effects Of Hsp70 ...mentioning
confidence: 77%
See 2 more Smart Citations
“…Suppression of endogenous enzymes involved in the formation of H 2 S in various diseases, or genetic defects in enzymatic systems of H 2 S biosynthesis lead to the development of various pathologies, including oncological, cardiovascular, neurodegenerative, autoimmune (rheumatoid arthritis, and asthma) pathologies [15][16][17][18]. In recent years, our studies of the protective properties of recombinant human Hsp70 and various H 2 S donors showed that these compounds protect cells from the action of LPS [6,11,19,20]. It is also known that elevated levels of H 2 S in cells can lead to the induction of Hsp70 formation [21].…”
Section: Introductionmentioning
confidence: 99%